Genotype FBN1/phenotype relationship in a cohort of patients with Marfan syndrome. Issue 2 (23rd November 2020) - Hernándiz, Amparo; Zúñiga, Angel; Valera, Francisco; Domingo, Diana; Ontoria‐Oviedo, Imelda; Marí, Jose F.; Román, Jose A.; Calvo, Inmaculada; Insa, Beatriz; Gómez, Rosa; Cervera, José V.; Miralles, Manuel; et al.
Abstract: Marfan syndrome (MFS) is a systemic connective tissue disorder caused by mutations in the fibrillin‐1 ( FBN1 ) gene, and cardiovascular involvement is the leading cause of mortality. We sought to examine the genotype/phenotype realtionship in 61 consecutive patients with a phenotype and genotype compatible with MFS. The FBN1 gene was analyzed by massive sequencing using a hybridization capture‐based target enrichment custom panel. Forty‐three different variants of FBN1 were identified, of which 17 have not been previously reported. The causal variants of MFS were grouped into mutations resulting in haploinsufficiency (HI group; 23 patients) and mutations producing a dominant‐negative effect (DN group; 38 patients). Patient information was collected from electronic medical records and clinical evaluation. While no significant differences were found between the two groups, the HI group included more cases with aortic dissection and occurring at a younger age that the DN group (34.7% vs. 15.8%; p = 0.160). Irrespective of the mutation group, males presented with a higher probability of aortic involvement (4‐fold higher risk than females) and aortic dissections events occurred at younger ages. Patients with DN variants carrying a cysteine substitution had a higher incidence of ectopia lentis . Abstract :